MISALIGNMENT DISTANCE ANALYSIS OF VIBRATION AND NOISE VALUE - Fathur Rahman Hidayat; Mastiadi Tamjidillah (Scientific Journal of Mechanical Engineering Kinematika, 2020)
This study aims to determine the vibration value that occurs during misalignment 0.1, 0.2, 0.3, 0.4, and 0.5 mm and determine the value of noise that occurs when misalignment 0.1, 0.2, 0.3, 0.4 and 0.5 mm. Variations used are parallel misalignment, angular misalignment and combination misalignment with a distance of misalignment 0.1, 0.2, 0.3, 0.4, and 0.5 mm. The results showed that the highest vibration and noise misalignment occurred when parallel misalignment 0.5 horizontal testing position was 8.97 mm / s overall velocity, 65.43 µm overall displacement, maximum noise 8 dB and carpet -6 dB, whereas for highest angular misalignment vibration and noise occur when angular misalignment 0.5 axial test position of 10.95 mm / s overall velocity, 76.95 µm overall displacement, maximum noise 5 dB carpet -11 dB and for the highest vibration and noise misalignment combination occurs when a combination of 0.5 mm axial misalignment test position is 16.33 mm / s overall velocity, 100.95 µm overall displacement noise maximum 13 dB and carpet 3 dB.